The Financial Behavior of Young Generation in Indonesia - Kurniasari, Irma; Sumiati; Ratnawati, Kusuma (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2023)
Purpose This study explored self-efficacy's link to student financial behavior, assessing its influence and dimensions. The aim was to improve financial literacy and behavior among students through interventions. The study deepened understanding of self-efficacy's role in university students' financial behavior. Design/methodology/approach In quantitative research, researchers employ SEM, specifically PLS, to examine self-efficacy and financial behavior in university students. The study has 100 student respondents and uses SEM-PLS for complex analysis, aiming to offer empirical evidence for hypotheses. Findings could significantly enrich comprehension of self-efficacy's influence on financial behavior in college students. Finding Results show a positive link between variables. Higher self-efficacy relates to improved financial behavior. Confident individuals budget, save, and make wise financial choices. This underscores the need to enhance self-efficacy in interventions for better student financial behavior. Overall, findings emphasize self-efficacy's pivotal role in shaping financial behavior. Research limitations/implications This study offers empirical evidence of a positive link between self-efficacy and financial behavior, broadening understanding. It highlights psychological factors in financial behavior and extends self-efficacy's role in financial management literature. Financial education programs should enhance self-efficacy for better financial management, benefiting students' overall well-being. Originality/value This research merges self-efficacy and financial behavior concepts, showcasing the link between psychological factors and financial actions. Combining these constructs provides a holistic view of how self-beliefs impact financial choices and behaviors.